Ramón Pané, las Primeras Décadas del Descubrimiento, el Caribe, Mayas, y la Supervivencia Biológica Nativa - Randle Sloan-Toraño (European Scientific Journal, ESJ, 2025)
El objetivo de este estudio es una investigación exhaustiva de la historiografía de América desde el descubrimiento hasta mediados del siglo XX diferenciando las analogías del manuscrito original de fray Ramón Pané realizado entre 1494 y 1498 y publicado en 1571. El estudio crítico de ese paralelismo refleja cómo los pueblos oriundos en la antigüedad caribeña y de América con anterioridad al descubrimiento del Nuevo Mundo perduraban íntimamente ligados a tierra, mar y cielo en una topografía orgánica y específica a cada parentela, tribu o nación. En esta revisión de la historia esas semejanzas entre las diversas naciones y sus entornos geográficos identifican como los originarios vivían una economía de seguridad en sus propias leyes y comunidades siendo dueños absolutos e integrados en una hermandad taumatúrgica y espiritual. Encontramos que en un corto plazo de décadas ese ambiente originario que contribuyó al perfeccionamiento de su atesoramiento mitológico y cultural en su propia cosmovisión entra en un grave peligro del cual numerosas comunidades no tenían escape.Este estudio sistematiza las semejanzas ancestrales compartidas entre el Caribe, Yucatán, Florida, Centroamérica y el norte de Sudamérica en sus conceptos mitológicos, cosmovisión, suicidios y muertes sacrificadas conforme a sus tradiciones y costumbres en el marco de sus propias diversidades. Se analiza esa trágica periodización histórica que fundamentó el suicidio cultural y personal masivo de los naturales caribeños. Durante esa primera década la mitología y cosmovisión de los naturales fue narrada por el ermitaño de la orden de San Jerónimo fray Ramón Pané cimentando la historia, origen y la herencia nativa caribeña. Este estudio específico de nuestra área geográfica presenta a Ramón Pané el autor del primer manuscrito de América por su valor histórico y antropológico aún poco estudiado desde la perspectiva de las semejanzas ancestrales de los naturales de América. The objective of this study is an exhaustive investigation of the historiography of America from the discovery until the middle of the 20th century, differentiating the analogies of the original manuscript by Friar Ramón Pané published in 1571, written between 1493 and 1498. This critical study of those parallelism reflects how the native peoples in ancient Caribbean and America prior to the discovery of the New World remained intimately linked to land, sea and sky in an organic topography specific to each family, tribe or nation. This study undertakes a critical look at how the native peoples of the Caribbean antiquity prior to the discovery of the New World were intimately  rooted to land, sea and sky in an organic topography specific to each family, tribe or nation. In our history review, the similarities between the various nations within their own natural geographical environments identify how the original people lived an economy of security in their laws and communities, being absolute owners and integrated into a thaumaturgical and spiritual brotherhood. We found that in a short period of decades that original environment that contributed to the perfection of their mythological and cultural treasures in their own worldview entered into a serious danger from which numerous communities had no escape. In a short period of decades, that original environment which contributed to the perfection of their mythological and cultural treasure in their own worldview entered into a serious danger from which numerous communities had no escape.This study systematizes the ancestral similarities shared between the Caribbean, Yucatan, Florida, Central America and northern South America in their mythological concepts, worldview, suicides and sacrificial deaths according to their traditions and customs within the framework of their own diversities. This tragic historical periodization that fundaments the massive cultural and personal suicide of Caribbean natives is analyzed. During that first decade, the mythology and worldview of the natives was narrated by the hermit of the order of San Jerónimo, Fray Ramón Pané, cementing the history, origin and native Caribbean heritage. This study in its specific geographical area presents Ramón Pané, the author of the first manuscript of America for its historical and anthropological significance still understudied from the perspective of the original natives and their ancestral similarities.